Comparing target volumes used in radiotherapy planning based on CT and PET/CT lung scans with and without respiratory gating applied - Janse van Rensburg, A. (University of Pretoria, 2013)
Dissertation (MSc (Medical Physics))--University of Pretoria, 2012.